The common good as an element of cooperation between non-governmental organizations and entrepreneurs - Poniatowski, Michał (Prawo Kanoniczne, 2023)
The article presents the issue of cooperation between non-governmental organizations and entrepreneurs for the common good. The article presents the definition of the parties to this cooperation as well as their heterogeneity. The analysis also concerns the purpose of cooperation in the form of the common good and its framework. The article also contains an analysis of the forms of this cooperation and the characteristic practical problems in this area. The most important conclusions are at the end of the article